The Roman Foundations of Public Law - Parham Mehraram; Godarz Eftekhar (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2019)
Public law as a discipline of legal science which considers public matters –in confront with private matter, is established in ancient Rome and influenced deeply the European history. In the first step, its basic concepts, such as Imperium and Jurisdictio, and its outlook toward the relation of power and law, gave way to the concept of sovereignty as a monopoly of approving, changing and abolishing of statutes. It leads to the establishment of authoritative governments. In the second step, it provides the proponents of absolutism with legal arguments against their traditional and new rivals. At the end, it were the constitutionalists who promote Roman law with some principle of roman private and corporate law and reinterpretation of old concepts in shadow of new needs of era to apply them against their oponents. Finally, these disputes resulted in our understanding of modern state and representation and Roman law, despite to its flexibility, leaved its lasting impression, i. e. formulation of political conflicts in the legal language.